Study of some physiologic properties of different genotype sweet corn hybrids - Lente, Ádám (Acta Agraria Debreceniensis, 2012)
The effect of nutrient-supply (control, N120+PK) and two different genotypes on the physiologic properties of sweet corn has been investigated in the crop-year of 2011 on chernozem soil in the Hajdúság region. The experiments were carried out at the Experimental Station of the University of Debrecen in Debrecen-Látókép. The experiment was sewn in two different sowing times: the 21st April can be considered as an early, while the 19th May as a late sowing time. The two involved hybrids were Jumbo and Enterprise. The applied plant density was 65 000 plants per hectare. Our aim with this experiment was to study the plant production, just as the main affecting factors of its development and dynamics, like nutrient-supply and genotypes. We aimed to study and analyse the relationships between these factors and plant production. In this study following parameters were measured and calculated: photosynthetic activity, chlorophyll-content (SPAD-value), leaf area index (LAI) and leaf area duration (LAD). Regarding the analysis of photosynthetic activity values no obvious relationship between the measured values and the applied hybrids, just as nutrient-supply has been revealed. Analysing the SPAD-values it can be stated that the chlorophyll-content of the measured leaves showed an increasing tendency due to the nutrient-supply. The highest values have been measured in the intensive cob development phase of the early sowing time plots. Regarding the LAI-values we have found significant differences between the fertilizer treatments in both sowing time treatments. In case of the leaf area duration values – that is derived from the LAI values – nutrient-supply has positively affected the duration of the assimilation area.